MORINGA OLEIFERA EXTRACT CAN INHIBIT GLOMERULUS DAMAGE OF RATTUS NOVERGICUS INJECTED CYCLOPHOSPHAMIDE - Laurencia Dwiamanda Elizabeth; Budhy, Theresia Indah; Rahayu, Retno Pudji (Universitas Airlangga, 2024)
Cyclophosphamide is a cytostatic used in chemotherapy. Cyclophosphamide has a toxic effect that causes damage to the kidneys. Moringa oleifera is a plant with high antioxidant activity. Its antioxidant content in the form of flavonoids and vitamin C which can inhibit glomerulus damage. Many studies have proven that Moringa oleifera contains high antioxidant activity. However, there has been no research about the potential of Moringa oleifera in inhibiting glomerulus damage that was injected with cyclophosphamide. The purpose of this study was to determine the potential of Moringa oleifera in inhibiting glomerulus damage in Rattus novergicus due to cyclophosphamide injection. This was a laboratory experiment with a post-test only control group design. This study used 18 Rattus norvegicus as samples which was divided into 3 sample groups namely K1 is the group that was only given NaCl, K2 was the group that was given NaCl and injected by cyclophosphamide, and the treatment group was given Moringa oleifera extract. Glomerulus histopathological preparations were stained with Hematoxylin Eosin. Data were analyzed statistically by the Kruskall Wallis and Mann-Whitney tests. The Mann-Whitney test showed significant difference between groups K1 and K2 and groups of P and K2 (p<0.05). There were no significant differences between K1 and P (p>0.05). Giving Moringa oleifera extract can inhibit the glomerular damage of Rattus novergicus, which is injected with cyclophosphamide.